The Degree to Which Middle School Mathematics Teachers Possess Creative Teaching Skills - Saif Karim Muslim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The present research aims to identify the degree to which middle school mathematics teachers possess creative teaching skills. To achieve this goal, the researcher adopted the descriptive methodology. The research population consisted of mathematics teachers teaching only at the middle school level in intermediate and secondary schools affiliated with the Al-Amarah District in the General Directorate of Education in Maysan, totaling (232) teachers. A randomly selected sample of (46) teachers constituted the main study sample.The research instrument was an observation checklist for creative teaching skills, consisting of (30) items distributed across the stages of creative teaching: (1) Creative Planning Skills, (2) Creative Implementation Skills, and (3) Creative Evaluation Skills). The validity and reliability of the instrument were verified, and it was applied to the sample after conducting statistical data analysis using SPSS. The results revealed:The degree to which middle school mathematics teachers possess creative teaching skills was moderate, but not at the desired level.There were no statistically significant differences in the degree of possession of creative teaching skills attributable to the gender variable.There were statistically significant differences in the degree of possession of creative teaching skills attributable to the experience variable, in favor of those with less than 10 years of teaching experience compared to those with 10 years or more.In light of the findings, a set of recommendations and suggestions were presented.